The impact of artificial intelligence in the travel and tourism industry: acceptance and adoption - Oliveira, Mariana Santos (2022)
The following thesis will focus on the general topic of Artificial Intelligence (AI). The main purpose of this work is to investigate how generally AI is being implemented and developed in modern times. Due to its magnitude, this research will focus on the travel and tourism industry. The research aims to get an overview of the impact of AI with particular attention to how it is implemented in the travel and tourism industry. The author compares existing data with a survey's results to better understand the correlation between people's beliefs and perceptions of AI and the resulting acceptance and adoption.